Impact of Dietary Yeast Supplementation on the Antioxidant Enzymes, Digestive Enzymes and Muscle Proximate Composition of Labeo rohita - Mustafa, Hassan; Aslam, Arslan; Ibrahim, Muhammad; Ullah, Zafar; Bhat, Sohail Nabi (Indus Journal of Bioscience Research, 2025)
The production of aquaculture has expanded rapidly to satisfy the rising demands of an expanding human population and by 2050 additional intensification is anticipated. Active dry yeasts are often used in probiotic products for their immune-stimulatory benefits, provided by vitamins, B-glucans, and nucleotides. The goal of the current study was to determine how dietary yeast used as a feed supplement, affected the muscle composition, digestive enzyme activity and antioxidant enzyme activity of Labeo rohita, taking into account the significance of this readily accessible and affordable source of protein and energy. The current experiment was carried out in indoor tank hatcheries. The current study indicated that adding dietary yeast to Labeo rohita's diet had a positive impact. All treatment groups and control group showed similar results of whole body proximate without any significant difference among treatments. Digestive enzymes analysis like protease with the highest activity observed in T4 (3.53U/mg), followed by T3 (3.31 U/mg), T2 (3.06 U/mg), T1 (2.65 U/mg) and T0 (2.34 U/mg) and amylase activity reaching its peak in T4 (4.84 U/mg), followed by T3 (4.66 U/mg), T2 (4.47 U/mg), T1 (4.32 U/mg) and T0 (4.19 U/mg). While lipase enzyme activity showed a non-significant trend (P > 0.05), indicating no differences between groups, protease and amylase showed significant results that rose significantly (P < 0.05) with larger yeast inclusion levels. Superoxide dismutase (SOD) and catalase enzyme activity were found to differ significantly by antioxidant enzyme analysis (P < 0.05), with T4 having the highest values (18.41 U/mg for SOD and 62.70 U/mg for catalase), and T0 having the lowest (10.87 U/mg for SOD and 55.67 U/mg for catalase). Peroxidase enzyme activity, on the other hand, showed a non-significant trend (P > 0.05) with slight variations between groups.